UPAYA MENINGKATKAN KUALITAS HASIL BELAJAR SISWA PADA POKOK BAHASAN MULTIKULTURAL MENGGUNAKAN MEDIA VIDEO DI SD - Hasibuan, Sulhan Efendi; Harahap, Asriana; Delfianis, Delfianis (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2021)
AbstractThe background of this study aims to determine how the description in cycle I and cycle II in an effort to improving the quality of the student learning outcomes (interest) on multicultural subjects using video media for classes IV at SDN 347 Batahan Mandailing Natal. Researchers also aims to determine changes after carrying out a cycle in the learning process so that the quality of the student learning outcomes increases with multicultural subjects using video media. The problems discussed in this thesis are how the students' interest in learning on multicultural subjects at SDN 347 Batahan, because in this school it seems clear that there is a lack of student interest in learning when attending lessons without any media assistance and is more related to Citizenship Education subjects so that students will tend to saturated. So the researcher is interested in conducting this research with the help of video media that is displayed on each material and in class meetings, so the researcher can see changes in student interest when carrying out the learning process from before. This researcher uses a qualitative type of classroom action research (CAR) model conducted at SDN 347 Batahan Mandailing Natal and the data collection instruments used were tests, observations, and interviews. To obtain data in this study, field research was carried out. Based on the discussion and research results, it can be seen that using video media on multicultural subjects to increase interest in learning at first can be assessed as less. However, the existence of this Classroom Action Research makes student interest in learning increase, this can be stated by an increase in interest in learning based on test results and observations. The results of student learning tests in the first cycle an average of 62.28% in the second cycle an average of 82.57%. While the results of observations on the teacher at each meeting in the first cycle of meeting I an average of 60% in the second meeting 75% and in the second cycle of the first meeting an average of 85%, the second meeting an average of 90%. Thus there is an increase in interest in learning in each cycle. Keywords: Quality Learning Outcomes, Video Media